First three-dimensional skull of the Middle Triassic mixosaurid ichthyosaur Phalarodon fraasi from Svalbard, Norway - Roberts, Aubrey Jane; Engelschiøn, Victoria Sjøholt; Hurum, Jørn Harald (Acta Palaeontologica Polonica, 2022)
The marine Middle Triassic sediments of Svalbard are rich in fossiliferous material and are particularly well-known for marine reptile fossils. Here, we present a new specimen of the small-bodied mixosaurid ichthyosaur Phalarodon fraasi from the Botneheia Formation. PMO 235.393 is unusual in being the first three-dimensional mixosaurid skull recovered from this formation, allowing us to use computed tomography to reconstruct the obscured right side of the cranium, resulting in the first 3D model available for a mixosaurid ichthyosaur. Although separated into different slabs, the specimen preserves most of the dermatocranium as well as some partial post-cranial elements. In particular, the rostrum, external naris, dentition, quadrate and sclerotic ring are well-preserved. This methodology gave new insights into the adaptations this taxon has to durophagy, as well as a detailed look at the heterodont dentition present in PMO 235.393. After comparing with other Phalarodon specimens, it was clear that the maxillary heterodonty of this genus is a synapomorphy. As such this was added as a new character in our phylogenetic analysis, supporting the separation of Phalarodon and Mixosaurus.